Indicadores de sustentabilidad en cría bovina del Este de Chaco, Argentina - Pellerano, Liliana Laura; Chavez Clemente, Maria Daniela; Calvi, Mariana; Balbuena, Osvaldo; Rosello Brajovich, José Emilio (INTA, 2022)
Poster